Kesan Penggunaan Gas Pelindung Berbeza Komposisi dalam Kimpalan Arka Logam terhadap Kekerasan Keluli Tahan Karat - NORIZAN, LIYANA (Research and Innovation in Technical and Vocational Education and Training, 2023)
All traditional welding procedures need the use of shielding gases. Shielding gases main purpose is to protect weld pool from the environment and to act as a conduit for the transfer of electricity from an electrode to the workpiece. The thickness of a weld neck and the altered grain structure of the welded zone area both affect how strong a connection is when it is being welded (between the heat affected zone and weld metal). This study uses stainless steel grades 304 and 316 as its test materials and as variables, carbon dioxide and a combination of 82% carbon dioxide and 18% argon are both used. A number of process variables are held constant in order to observe the differences similar for various types of gas. These variables include the welding speed, the size of the workpieces, and the welding angle. Samples from the workpiece were collected and subjected to a Rockwell hardness test. These testing provide information on the mechanical properties of both types of stainless steel after being welded using the two different types of shielding gas aforementioned. The findings indicate that stainless steel 316 is harder than stainless steel 304. It is also discovered, the usage of shielding gas mixture develops harder steels compared to single type shielding gas.